Benefits of a Department of Corrections Partnership With a Health Sciences University: New Jersey's Experience. (April 2014) - Reeves, Rusty; Brewer, Arthur; DeBilio, Lisa; Kosseff, Christopher; Dickert, Jeff
More than half of the state prisons in the United States outsource health care. While most states contract with private companies, a small number of states have reached out to their health science universities to meet their needs for health care of prisoners. New Jersey is the most recent state to form such an agreement. This article discusses the benefits of such a model for New Jersey's Department of Corrections and for New Jersey's health sciences university, the Rutgers University, formerly the University of Medicine and Dentistry of New Jersey. The benefits for both institutions should encourage other states to participate in such affiliations.